Explaining rising returns to education in urban China in the 1990s - Xuejun Liu; Albert Park; Yaohui Zhao (Institute for the Study of Labor (IZA), 2010)
Although theory predicts that international trade will decrease the relative demand for skilled workers in relatively skill-deficit countries, in recent decades many developing countries have experienced rising wage premiums for skilled workers. We examines this puzzle by quantifying the relative importance of different supply and demand factors in explaining the rapid increase in the returns to education experienced by China during the 1990s. Analyzing Chinese urban household survey and census data for six provinces, we find that although changes in the structure of demand did reduce the demand for skilled workers, consistent with trade theory, the magnitude of the effect was modest and more than offset by institutional reforms and technological changes that increased the relative demand for skill.
Keywords: F16; J24; J31; P23; 330; Education; earnings; inequality; China; Bildungsertrag; Hochqualifizierte Arbeitskräfte; Lohnstruktur; Qualifikation; Städtischer Arbeitsmarkt; China